Systematic druggable genome-wide Mendelian randomization identifies therapeutic targets for osteoporosis - Chiyun Sun; Ruikang Liu; Jiaming Hu; Weiming Fan; Chuanrui Sun; Pengcheng Shan; Xu Wei (Osteoporosis and Sarcopenia, 2025)
Objectives: The aim of this study was to find potential drug targets of osteoporosis (OP) through systematic druggable genome-wide Mendelian randomization (MR) analysis. Methods: Combining the multi-omics data, we utilized drug target MR and mediation MR to search for potential drug targets of OP and their possible pathways. Functional enrichment analyses were used to identify metabolic pathways of potential drug targets. In addition, we performed a two-sample MR analysis to investigate the causal relationship between immunoexpression and OP. Finally, we conducted Phe-MR analysis and drug prediction to determine the indications, potential side effects, and pharmacological activities of previously tested targets. Results: We screened three potential targets of OP-TAS1R3, TMX2, and SREBF1. Mediation MR analysis revealed that body mass index, type 2 diabetes, and chemokine C-C motif ligand 4 may be mediators for the above targets to act on OP. The Steiger Filtering test did not find a reverse causality. The results of functional enrichment analysis showed that the identified target genes may affect OP through lipid metabolism, immune expression, and insulin resistance. Two-sample MR analysis showed that HLA-DR expression in multiple monocyte subpopulations was associated with OP. The five drugs including sucrose, mirtazapine, aspartame, ginsenoside and ezetimibe are identified as the most probable candidates for the treatment of OP. Phe-MR found that TAS1R3 was associated with lower systolic blood pressure, TMX2 with neurologic and lipid metabolism, and SREBF1 with muscle power. Conclusions: Our study provides evidence support for TAS1R3, TMX2, and SREBF1 as drug targets for OP.